2006
DOI: 10.1185/030079906x89784
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic moderate-to-severe non-malignant pain with polymer-coated extended-release morphine sulfate capsules

Abstract: P-ERMS was efficacious and well tolerated in patients with chronic, moderate-to-severe, non-malignant pain when used once or twice daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…In general, studies on kappa agonistsantagonists indicate greater analgesia in women than men 53 , but studies of sex differences in response to µ-agonists, such as morphine, have yielded conflicting results [53][54][55][56] , likely due to differences in clinical pain vs. experimental pain, modality and intensity of pain stimulus used, opioid type and dose, experimental design and data analytic techniques 53,55,57 . Previous studies specific to P-ERMS and CRO have demonstrated similar outcomes regardless of sex 19,21 .…”
Section: Study Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…In general, studies on kappa agonistsantagonists indicate greater analgesia in women than men 53 , but studies of sex differences in response to µ-agonists, such as morphine, have yielded conflicting results [53][54][55][56] , likely due to differences in clinical pain vs. experimental pain, modality and intensity of pain stimulus used, opioid type and dose, experimental design and data analytic techniques 53,55,57 . Previous studies specific to P-ERMS and CRO have demonstrated similar outcomes regardless of sex 19,21 .…”
Section: Study Limitationsmentioning
confidence: 84%
“…The T max was longer than that with another QD morphine sulfate capsule 16 . The results of the KADIAN: Response Of Nonmalignant, Under-treated Subjects with Moderate/Severe Pain (KRONUS-MSP) trial show that P-ERMS is well tolerated and associated with significant improvement in pain, sleep and quality-of-life measures in patients with chronic, moderate to severe, nonmalignant pain 19 . A retrospective study of long-term use of P-ERMS in patients with chronic, nonmalignant pain indicated that these patients could maintain efficacy without escalation in dose strength or frequency 20 .…”
Section: Introductionmentioning
confidence: 99%
“…One study randomized patients with chronic pain who were not adequately relieved with their current therapy to an extended-release morphine preparation. 149 Improvements were reported in pain and sleep scores, physical and mental component scores of the SF-36v2 Health Survey, and patient and clinician global assessment scores. 149 Instructions for the conversions to a long-acting opioid from a short-acting agent are usually found in the Prescribing Information for individual drugs.…”
Section: Long-acting Opioidsmentioning
confidence: 99%
“…In the KRONUS‐MSP (KADIAN ® : Response Of Non‐malignant, Under‐treated Subjects with Moderate/Severe Pain) trial, the efficacy and tolerability of KADIAN ® were evaluated for the treatment of chronic, moderate‐to‐severe, nonmalignant pain [visual numeric scale (VNS) pain score ≥ 4] in 1428 patients who had been inadequately treated with other opioids. In this large, prospective trial, patients were randomised to receive KADIAN ® q24 h in the morning or evening for a 4‐week period (33). Treatment was initiated q24 h, with dose increases allowed after week 1 or 2.…”
Section: Clinical Trials In Nonmalignant Painmentioning
confidence: 99%
“…Quality‐of‐life and clinician global assessments were analysed at baseline and week 4. Additional follow‐up, to determine continued usage and global assessment of therapy, was requested 1 month after trial completion and obtained via a business reply card (BRC) (33). Improvements in Pain VNS score, Sleep VNS score, SF‐36v2™ score (34) and Patient and Clinician Global Assessment of Therapy scores were used to measure efficacy outcomes (33).…”
Section: Clinical Trials In Nonmalignant Painmentioning
confidence: 99%